A high-solid-content single-walled carbon nanotube aqueous conductive slurry formula composition and preparation method thereof

The single-wall carbon nanotube powder is cut short by a three-roll grinder, and combined with the homogenization of the dispersant and high-pressure microjet homogenizer, the problem of uneven dispersion of single-wall carbon nanotubes is solved, and the stable dispersion and conductive performance of high-solid aqueous conductive paste is achieved, and the mass energy density of battery materials is improved.

CN119763899APending Publication Date: 2025-04-04NINGBO XENWO NEW MATERIAL TECH CO LTD
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202510159954.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform dispersion of high-solid single-wall carbon nanotubes, resulting in a decrease in conductivity and limited improvement in mass energy density of battery materials.

Method used

The single-wall carbon nanotube powder is cut short by a three-roll grinder, and combined with the homogenization of dispersant, dispersing additive and high-pressure microjet homogenizer, the depolymerization and stable dispersion of single-wall carbon nanotubes in aqueous media is achieved.

Benefits of technology

The stable dispersion and improvement of the conductivity of the aqueous conductive paste of high-solid single-wall carbon nanotubes is achieved, ensuring the high-quality energy density and long life of the battery material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119763899A_ABST
    Figure CN119763899A_ABST
Patent Text Reader

Abstract

The invention discloses a high-solid-content single-walled carbon nanotube aqueous conductive slurry formula composition and a preparation method thereof, belonging to the technical field of conductive slurry. The raw materials include single-walled carbon nanotube powder, dispersant, dispersing aid, pH regulator and deionized water. The invention innovatively proposes to shorten the single-walled carbon nanotube powder with the aid of a three-roll grinder, grind the single-walled carbon nanotube powder, the dispersant, the dispersing aid and the like into fibers of less than 10 μm under the forward shear force of the three-roll grinder, and the van der Waals force between the shorter single-walled carbon nanotube bundles is relatively weak and easier to be opened, so that the homogenization pressure of the subsequent high-pressure microfluidizer is ≤1000 bar, and the single-walled carbon nanotubes are uniformly dispersed under a relatively low homogenization pressure. While opening the single-walled carbon nanotube bundles, the problem of damage to the length size of the carbon nanotubes under a higher homogenization pressure is avoided, thereby ensuring the conductivity of the high-solid-content single-walled carbon nanotube aqueous conductive slurry formula composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive pastes, and in particular relates to a high-solid-content single-walled carbon nanotube aqueous conductive paste formula composition and a preparation method thereof. Background Art

[0002] Compared with multi-walled carbon nanotubes, carbon black and other conductive additives, single-walled carbon nanotubes have a higher aspect ratio and better flexibility. They can cover the surface of silicon-based particles and establish a three-dimensional network connection between silicon-based particles. Therefore, the electrical contact between single-walled carbon nanotubes and active materials has obvious advantages over other conductive additives. While playing a conductive role, the three-dimensional network of single-walled carbon nanotubes can also inhibit stress cracking and even pulverization of active material particles caused by volume expansion during the cycle of silicon-based negative electrodes. At the same time, it can build conductive bridges between cracked active materials to maintain a complete three-dimensional conductive network. Studies have shown that single-walled carbon nanotubes can form a three-dimensional conductive network at extremely low addition amounts (0.01%). When applied to silicon-based negative electrodes, they can achieve more than 1,500 stable cycles and high-rate charging of up to 4C under battery specific energy conditions of up to 300Wh / kg and 800Wh / L.

[0003] Single-walled carbon nanotubes are nanoscale fiber materials that have both the strong agglomeration effect of nanopowders and the entanglement and bonding phenomenon of fiber materials. Due to the superposition of various effects, the agglomerates of single-walled carbon nanotubes have greater adsorption, tighter bonding, and more difficult to disperse. Therefore, to obtain uniformly dispersed carbon nanotubes, the following conditions must be met at the same time: destroying the entanglement and bonding state of long fibers, overcoming the strong adsorption of agglomerates, and stabilizing the dispersion state of carbon nanotubes.

[0004] Mechanical stirring and grinding can only mix carbon nanotube aggregates with the matrix powder on a macro scale, but have a poor dispersion effect on the carbon nanotube aggregates themselves; ultrasound and ball milling can break up the carbon nanotubes and disperse the carbon nanotube aggregates, but will also make the carbon nanotubes more densely bonded together; adding surfactants and acid-base washing methods can break and disperse the flocculent single-walled carbon nanotubes on the surface of the aggregates, but the effect is not significant for single-walled carbon nanotubes that are tightly entangled.

[0005] The use of a high-pressure microfluidizer can depolymerize the single-walled carbon nanotube bundle under a relatively high pressure, but it will cause the single-walled carbon nanotubes to be broken, and the conductivity of the slurry will also decrease after the length is reduced, making it difficult to obtain a high-solid-content single-walled carbon nanotube conductive slurry. At present, the single-walled carbon nanotube content of the conductive slurry is generally less than 0.6%. This will cause the thickness of the dry film applied to the pole piece after mixing with the battery material to be reduced, limiting the improvement of the mass energy density of the single battery cell. Therefore, the development of a high-solid-content single-walled carbon nanotube water-based conductive slurry formula composition and its preparation method is an urgent problem to be solved in the field. Summary of the invention

[0006] The purpose of the present invention is to provide a high-solid content single-walled carbon nanotube aqueous conductive slurry formula composition and a preparation method thereof, wherein the single-walled carbon nanotube powder is shortened by a three-roll grinder, and is infiltrated with a dispersant and a dispersing aid, etc., and the homogenization effect of a high-pressure microfluidizer is combined to achieve the depolymerization and stable dispersion of the single-walled carbon nanotubes in an aqueous medium.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A high-solid content single-walled carbon nanotube aqueous conductive slurry formula composition comprises the following raw materials in parts by mass:

[0009] 0.6-1.0 parts of single-walled carbon nanotube powder;

[0010] Dispersant 1.2-2.0 parts;

[0011] Dispersing aid 0.6-1.2 parts;

[0012] 0.5-2.0 parts of pH regulator;

[0013] 93.8-97.1 parts of deionized water.

[0014] Furthermore, the solid content of the high-solid-content single-walled carbon nanotube aqueous conductive paste formula composition is 2.9% to 6.2%.

[0015] Furthermore, the viscosity of the high solid content single-walled carbon nanotube aqueous conductive paste formula composition is 8000-30000 cps.

[0016] Furthermore, the particle size of the single-walled carbon nanotube powder is 10-50 μm, and the purity of the carbon component is greater than 98%.

[0017] Furthermore, the content of single-walled carbon nanotube bundles in the single-walled carbon nanotube powder is greater than 80%, and the rest is impurities such as double-walled carbon nanotubes, few-walled carbon nanotubes and amorphous carbon.

[0018] Furthermore, the single-walled carbon nanotube bundle consists of 1 to 10 single-walled carbon nanotubes.

[0019] Furthermore, the diameter of the single-walled carbon nanotube is 1.3-2.0 nm, and the aspect ratio is greater than 1000.

[0020] Furthermore, the graphitization degree of single-walled carbon nanotubes is greater than 20, that is, Raman I G / I D >20.

[0021] Furthermore, the specific surface area of ​​single-walled carbon nanotubes is >500 m 2 / g.

[0022] A method for preparing a high-solid content single-walled carbon nanotube aqueous conductive slurry formula composition,

[0023] Furthermore, the dispersant is sodium carboxymethyl cellulose with a degree of substitution of 0.55 to 1.05.

[0024] Furthermore, the dispersing aid is prepared by mixing polyvinyl pyrrolidone and comb-shaped polyamide lithium salt in a mass ratio of 2.5 to 3:1.

[0025] Furthermore, the pH adjuster is a multifunctional amine auxiliary agent AMP-95, which adjusts the pH value of the high-solid single-walled carbon nanotube aqueous conductive paste formula composition to 7.5-9.5.

[0026] Further, the comb-like polyamide lithium salt is prepared by the following steps:

[0027] The methoxy polyether amine is stirred and dissolved in N, N-dimethylformamide to obtain a methoxy polyether amine solution with a mass fraction of 35%, and the 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride is stirred and dissolved in N, N-dimethylformamide to obtain a 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride solution with a mass fraction of 9.5%;

[0028] The methoxy polyether amine solution is added into the reaction kettle, and the 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride solution is added dropwise into the reaction kettle at 45-50°C and 200-300r / min. After the addition is completed, lithium carbonate is added, and the reaction is stirred at 70-75°C for 2.5-3h. The carboxylic acid dianhydride at both ends of the 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride solution is ring-opened and reacted with the amino group of the methoxy polyether amine. The carboxyl group formed partially after the ring-opening reacts with lithium carbonate to form a carboxylic acid lithium salt. The reaction is cooled to -10°C, filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a comb-like polyamide lithium salt.

[0029] Furthermore, the usage ratio of the methoxy polyetheramine solution, the 3,3',4,4'-benzophenonetetracarboxylic dianhydride solution and the lithium carbonate is 20 mL:20 mL:0.1 g.

[0030] A method for preparing a high-solid content single-walled carbon nanotube aqueous conductive slurry formula composition comprises the following steps:

[0031] Step 1: Mix the dispersant, dispersing aid and deionized water, perform ultrasonic dispersion for 15 to 20 minutes, and adjust the viscosity of the dispersion to 300 to 1000 cps to obtain a dispersion medium.

[0032] Step 2: Mix the single-walled carbon nanotube powder and the dispersion medium evenly, then transfer to a mixing and degassing machine, stir and degas at a vacuum degree of -30 to -80 kPa and a stirring speed of 1500 to 2000 r / min, and then transfer to a three-roll grinder for grinding and dispersion 1 to 3 times to obtain a single-walled carbon nanotube pre-dispersion.

[0033] Step 3: Add the pH regulator and deionized water into the single-walled carbon nanotube pre-dispersion according to the raw material ratio, transfer it to a high-pressure microfluidizer and homogenize and disperse it at a homogenization pressure of 600-1000 bar to obtain a high-solid single-walled carbon nanotube aqueous conductive slurry formula composition.

[0034] Furthermore, the three-roller grinding machine includes three rollers, namely roller No. 1, roller No. 2 and roller No. 3, the roller diameters are 50 mm to 120 mm, the rollers are made of zirconia ceramics, and the runout accuracy is 1 um.

[0035] Furthermore, the specific method of grinding and dispersing is: setting the grinding parameters, the grinding parameters are: the gap between roller No. 1 and roller No. 2 is 300um, the gap between roller No. 2 and roller No. 3 is 150um, and grinding is carried out at a speed of 500rpm for 1 to 3 times; the gap between roller No. 1 and roller No. 2 is 150um, the gap between roller No. 2 and roller No. 3 is 75um, and grinding is carried out at a speed of 500rpm for 1 to 3 times; the gap between roller No. 1 and roller No. 2 is 50um, the gap between roller No. 2 and roller No. 3 is 25um, and grinding is carried out at a speed of 500rpm for 1 to 3 times; the gap between roller No. 1 and roller No. 2 is 20um, the gap between roller No. 2 and roller No. 3 is 10um, and grinding is carried out at a speed of 500rpm for 1 to 3 times.

[0036] Beneficial effects of the present invention:

[0037] 1. The present invention innovatively proposes to shorten the single-walled carbon nanotube powder with the aid of a three-roll grinder, and grind the single-walled carbon nanotube powder, dispersant, dispersing aid, etc. into fibers less than 10 um under the forward shear force of the three-roll grinder. The van der Waals force between the shorter single-walled carbon nanotube bundles is relatively weak and is easier to open, thereby facilitating the subsequent homogenization pressure of the high-pressure microfluidizer to be ≤1000 bar, ensuring uniform dispersion of the single-walled carbon nanotubes under a lower homogenization pressure, opening the single-walled carbon nanotube bundles, and avoiding the problem of damage to the length size of the carbon nanotubes under a higher homogenization pressure, thereby ensuring the conductivity of the high-solid content single-walled carbon nanotube aqueous conductive slurry formula composition.

[0038] 2. The dispersant of the present invention is sodium carboxymethyl cellulose with a substitution degree of 0.55 to 1.05, that is, the number of hydrogens in the three hydroxyl groups of the glucose unit in the sodium carboxymethyl cellulose replaced by carboxymethyl groups is 0.55 to 1.05, which helps to play the role of stabilizer, thickener, dispersant and binder. The auxiliary dispersant includes polyvinyl pyrrolidone and comb-shaped polyamide lithium salt. The molecular weight of polyvinyl pyrrolidone is relatively large, which can play a steric hindrance role and prevent the dispersed single-walled carbon nanotube bundles from agglomerating again to form agglomerates; the benzene ring structure in the comb-shaped polyamide lithium salt is adsorbed on the single-walled carbon nanotubes through π-π interaction, and the terminal carboxylic acid lithium salt forms an electrostatic repulsion on the aqueous conductive paste formula composition, which helps to enhance the steric repulsion effect between the single-walled carbon nanotube bundles and helps to stabilize the dispersion of the high-solid content single-walled carbon nanotube aqueous conductive paste formula composition. The multifunctional amine auxiliary agent AMP-95 is used as a pH regulator to help adjust the Zeta potential of the aqueous conductive paste formula composition in the dispersion system, and further improve the stability of the dispersion system by enhancing the electrostatic repulsion of the system. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The present invention will be further described below in conjunction with the accompanying drawings.

[0040] Figure 1 This is an atomic force microscope image of the high solid content single-walled carbon nanotube aqueous conductive paste formulation composition in Example 2 of the present invention;

[0041] Figure 2 This is a transmission electron microscope picture of the high solid content single-walled carbon nanotube aqueous conductive paste formula composition in Example 2 of the present invention. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1: This example provides a high solid content single-walled carbon nanotube aqueous conductive slurry formulation composition, which is prepared by the following method:

[0044] S1: Dissolve methoxy polyether amine with N, N-dimethylformamide by stirring to obtain a methoxy polyether amine solution with a mass fraction of 35%, and dissolve 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride with N, N-dimethylformamide by stirring to obtain a 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride solution with a mass fraction of 9.5%; add 2L of methoxy polyether amine solution into a reactor, and drop 2L of 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride solution into the reactor at 45°C and 200r / min. After the dropwise addition is completed, add 0.01kg of lithium carbonate, stir and react at 70°C for 2.5h, cool to -10°C, filter, and rotary evaporate the filtrate to remove the solvent to obtain a comb-like polyamide lithium salt.

[0045] S2: polyvinyl pyrrolidone with a molecular weight of 10,000 and comb-like polyamide lithium salt are mixed in a mass ratio of 2.5:1 to obtain a dispersing aid; sodium carboxymethyl cellulose with a degree of substitution of 0.55 as a dispersant, the dispersing aid and deionized water are mixed, ultrasonically dispersed for 15 minutes, and the viscosity of the dispersion is adjusted to 300 cps to obtain a dispersion medium.

[0046] S3: Mix the single-walled carbon nanotube powder and the dispersion medium evenly, then transfer to a mixing and degassing machine, stir and degas at a vacuum degree of -30kPa and a stirring speed of 1500r / min, and then transfer to a three-roll grinder; the roller diameter of the three-roll grinder is 50mmmm, the roller material is zirconia ceramic, and the runout accuracy is 1um; the three-roll grinder includes three rollers, roller 1, roller 2 and roller 3, the gap between roller 1 and roller 2 is 300um, and the gap between roller 2 and roller 3 is 1um. The gap is 150um, and the grinding is performed once at a speed of 500rpm; the gap between roller No. 1 and roller No. 2 is 150um, the gap between roller No. 2 and roller No. 3 is 75um, and the grinding is performed once at a speed of 500rpm; the gap between roller No. 1 and roller No. 2 is 50um, the gap between roller No. 2 and roller No. 3 is 25um, and the grinding is performed once at a speed of 500rpm; the gap between roller No. 1 and roller No. 2 is 20um, the gap between roller No. 2 and roller No. 3 is 10um, and the grinding is performed once at a speed of 500rpm to obtain a single-walled carbon nanotube predispersion.

[0047] S4: Add AMP-95 multifunctional amine additive as a pH regulator and deionized water into the single-walled carbon nanotube pre-dispersion according to the raw material ratio, transfer it to a high-pressure microfluidizer and homogenize and disperse it at a homogenization pressure of 600 bar to obtain a high-solid content single-walled carbon nanotube aqueous conductive slurry formula composition.

[0048] The high solid content single-walled carbon nanotube aqueous conductive paste formula composition has a viscosity of 8000cps, a solid content of 2.9%, and a pH value of 7.5. The mass concentration of each raw material is as follows:

[0049] Single-walled carbon nanotube powder 0.6%; dispersant 1.2%; dispersing aid 0.6%; pH adjuster 0.5%; deionized water 97.1%.

[0050] Example 2: This example provides a high solid content single-walled carbon nanotube aqueous conductive slurry formulation composition, which is prepared by the following method:

[0051] S1: Dissolve methoxy polyether amine with N, N-dimethylformamide by stirring to obtain a methoxy polyether amine solution with a mass fraction of 35%, and dissolve 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride with N, N-dimethylformamide by stirring to obtain a 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride solution with a mass fraction of 9.5%; add 2L of methoxy polyether amine solution into a reactor, and drop 2L of 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride solution into the reactor at 48°C and 250r / min. After the dropwise addition is completed, add 0.01kg of lithium carbonate, stir and react at 72°C for 2.8h, cool to -10°C, filter, and rotary evaporate the filtrate to remove the solvent to obtain a comb-like polyamide lithium salt.

[0052] S2: polyvinyl pyrrolidone with a molecular weight of 20,000 and comb-like polyamide lithium salt are mixed in a mass ratio of 2.8:1 to obtain a dispersing aid; sodium carboxymethyl cellulose with a degree of substitution of 0.8 as a dispersant, the dispersing aid and deionized water are mixed, ultrasonically dispersed for 18 minutes, and the viscosity of the dispersion is adjusted to 600 cps to obtain a dispersion medium.

[0053] S3: The single-walled carbon nanotube powder and the dispersion medium are mixed evenly, and then transferred to a mixing and degassing machine, stirred and degassed at a vacuum degree of -50kPa and a stirring speed of 1800r / min, and then transferred to a three-roll grinder; the roller diameter of the three-roll grinder is 90mm, the roller material is zirconia ceramic, and the runout accuracy is 1um; the three-roll grinder includes three rollers, roller 1, roller 2 and roller 3, the gap between roller 1 and roller 2 is 300um, and the gap between roller 2 and roller 3 is 100um. The gap between roller No. 1 and roller No. 2 is 150um, and the gap between roller No. 2 and roller No. 3 is 75um, and the gap between roller No. 1 and roller No. 2 is 50um, and the gap between roller No. 2 and roller No. 3 is 25um, and the gap between roller No. 1 and roller No. 2 is 25um, and the gap between roller No. 2 and roller No. 3 is 20um, and the gap between roller No. 1 and roller No. 2 is 10um, and the gap between roller No. 2 and roller No. 3 is 10um, and the gap between roller No. 1 and roller No. 2 is 10um, and the gap between roller No. 2 and roller No. 3 is 10um, and the gap between roller No. 1 and roller No. 2 is 20um, and the gap between roller No. 2 and roller No. 3 is 1 ...

[0054] S4: Add AMP-95 multifunctional amine additive as a pH regulator and deionized water into the single-walled carbon nanotube pre-dispersion according to the raw material ratio, transfer it to a high-pressure microfluidizer and homogenize and disperse it at a homogenization pressure of 800 bar to obtain a high-solid content single-walled carbon nanotube aqueous conductive slurry formula composition.

[0055] The high solid content single-walled carbon nanotube aqueous conductive paste formula composition has a viscosity of 18000 cps, a solid content of 2.9% to 6.2%, a pH value of 8, and a mass concentration of each raw material is as follows:

[0056] Single-walled carbon nanotube powder 0.8%; dispersant 1.6%; dispersing aid 0.9%; pH adjuster 1.2%; deionized water 95.5%.

[0057] Taking Example 2 as a typical example, the high solid content single-walled carbon nanotube aqueous conductive paste formulation composition was observed. Figure 1 and Figure 2 .

[0058] Depend on Figure 1 It can be seen that the single-walled carbon nanotube bundles in the conductive paste formula composition are uniformly dispersed, and the length of the single-walled carbon nanotube bundles is less than 10 μm. Figure 2 It can be seen that the single-walled carbon nanotube bundle consists of 1 to 10 single-walled carbon nanotubes.

[0059] Example 3: This example provides a high solid content single-walled carbon nanotube aqueous conductive slurry formulation composition, which is prepared by the following method:

[0060] S1: Dissolve methoxy polyether amine with N, N-dimethylformamide by stirring to obtain a methoxy polyether amine solution with a mass fraction of 35%, and dissolve 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride with N, N-dimethylformamide by stirring to obtain a 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride solution with a mass fraction of 9.5%; add 2L of methoxy polyether amine solution into a reactor, and drop 2L of 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride solution into the reactor at 50°C and 300r / min. After the dropwise addition is completed, add 0.01kg of lithium carbonate, stir and react at 75°C for 3h, cool to -10°C, filter, and rotary evaporate the filtrate to remove the solvent to obtain a comb-like polyamide lithium salt.

[0061] S2: polyvinyl pyrrolidone with a molecular weight of 30,000 and comb-like polyamide lithium salt are mixed in a mass ratio of 3:1 to obtain a dispersing aid; sodium carboxymethyl cellulose with a degree of substitution of 1.05 as a dispersant, the dispersing aid and deionized water are mixed, ultrasonically dispersed for 20 minutes, and the viscosity of the dispersion is adjusted to 1000 cps to obtain a dispersion medium.

[0062] S3: Mix the single-walled carbon nanotube powder and the dispersion medium evenly, then transfer to a mixing and degassing machine, stir and degas at a vacuum degree of -80kPa and a stirring speed of 2000r / min, and then transfer to a three-roll grinder; the roller diameter of the three-roll grinder is 120mm, the roller material is zirconia ceramic, and the runout accuracy is 1um; the three-roll grinder includes three rollers, roller No. 1, roller No. 2 and roller No. 3, the gap between roller No. 1 and roller No. 2 is 300um, and the gap between roller No. 2 and roller No. 3 is 100um. The gap is 150um, and the grinding is performed 3 times at a speed of 500rpm; the gap between roller No. 1 and roller No. 2 is 150um, the gap between roller No. 2 and roller No. 3 is 75um, and the grinding is performed 3 times at a speed of 500rpm; the gap between roller No. 1 and roller No. 2 is 50um, the gap between roller No. 2 and roller No. 3 is 25um, and the grinding is performed 3 times at a speed of 500rpm; the gap between roller No. 1 and roller No. 2 is 20um, the gap between roller No. 2 and roller No. 3 is 10um, and the grinding is performed 3 times at a speed of 500rpm to obtain a single-walled carbon nanotube predispersion.

[0063] S4: Add AMP-95 multifunctional amine additive as a pH regulator and deionized water into the single-walled carbon nanotube pre-dispersion according to the raw material ratio, transfer it to a high-pressure microfluidizer and homogenize and disperse it at a homogenization pressure of 1000 bar to obtain a high-solid content single-walled carbon nanotube aqueous conductive slurry formula composition.

[0064] The high solid content single-walled carbon nanotube aqueous conductive paste formula composition has a viscosity of 30,000 cps, a solid content of 6.2%, and a pH value of 9.5. The mass concentration of each raw material is as follows:

[0065] Single-walled carbon nanotube powder 1.0%; dispersant 2.0%; dispersing aid 1.2%; pH adjuster 2.0%; deionized water 93.8%.

[0066] The particle size of the single-walled carbon nanotube powder used in Examples 1 to 3 is 10 to 50 μm, and the purity of the carbon component is > 98%. The content of the single-walled carbon nanotube bundle in the single-walled carbon nanotube powder is > 80%, and the rest is impurities such as double-walled carbon nanotubes, few-walled carbon nanotubes and amorphous carbon. The graphitization degree of the single-walled carbon nanotube is > 20, that is, the Raman I G / I D >20. The specific surface area of ​​single-walled carbon nanotubes is >500m 2 / g.

[0067] The single-walled carbon nanotube bundle in the high-solid single-walled carbon nanotube aqueous conductive slurry formula composition consists of 1 to 10 single-walled carbon nanotubes. The diameter of the single-walled carbon nanotube is 1.3 to 2.0 nm, and the aspect ratio is greater than 1000.

[0068] Comparative Example 1: On the basis of Example 2, without being processed by the three-roll grinder in step S3, the single-walled carbon nanotube powder, the dispersion medium in step S2, the AMP-95 multifunctional amine additive as a pH adjuster and deionized water are directly mixed according to the raw material ratio, transferred to a high-pressure microfluidizer and homogenized and dispersed at a homogenization pressure of 600 to 1000 bar, and the other steps remain unchanged to obtain a high-solid single-walled carbon nanotube aqueous conductive slurry formula composition.

[0069] Comparative Example 2: Based on Example 2, no comb-shaped polyamide lithium salt is added, polyvinyl pyrrolidone is directly used as a dispersant in step S2, and the other steps remain unchanged to obtain a high-solid content single-walled carbon nanotube aqueous conductive slurry formula composition.

[0070] The performance tests were performed on Examples 1 to 3 and Comparative Examples 1 to 2.

[0071] Take 25mL of different high-solid single-walled carbon nanotube water-based conductive paste formula compositions and place them in transparent glass bottles with a volume of 30mL to obtain different samples. Let them stand at room temperature of 26±2℃ for 30 days, observe and record the agglomeration and sedimentation of the samples in different glass bottles; use TQC VF2106 fineness detection scraper to scrape the high-solid single-walled carbon nanotube water-based conductive paste formula combination after standing for 30 days, and observe whether there are particles in the range of 0-50μm on the fineness meter. Combined with the evaluation of the dispersion stability of different high-solid single-walled carbon nanotube water-based conductive paste formula compositions, the results are shown in Table 1:

[0072] Table 1 Dispersion stability results of different high solid content single-walled carbon nanotube aqueous conductive paste formulation compositions

[0073] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Agglomeration and sedimentation none none none none A small amount of sedimentation Are there particles? none none none A small amount of particles A small amount of particles

[0074] It can be seen from Table 1 that the high solid content single-walled carbon nanotube aqueous conductive paste formulation compositions in Examples 1 to 3 have better dispersion stability.

[0075] Comparative Example 1 shows that compared with the traditional high pressure (>1000 bar), the homogenization pressure of the high-pressure microfluidizer in the embodiment is ≤1000 bar, indicating that after the three-roll mill is used for grinding, the single-walled carbon nanotube powder can also obtain a good dispersion effect under low-pressure homogenization conditions. Comparative Example 2 shows that the comb-like polyamide lithium salt combined with polyvinyl pyrrolidone as a dispersant can improve the dispersion stability of the high-solid single-walled carbon nanotube aqueous conductive paste formula composition.

[0076] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high solid content single-walled carbon nanotube aqueous conductive slurry formulation composition, characterized in that: The following raw materials are included by mass: The dispersing aid is prepared by mixing polyvinyl pyrrolidone and comb-shaped polyamide lithium salt in a mass ratio of 2.5 to 3:

1.

2. The high solid content single-walled carbon nanotube aqueous conductive paste composition according to claim 1, characterized in that: The content of the single-walled carbon nanotube bundle in the single-walled carbon nanotube powder is greater than 80%, and the single-walled carbon nanotube bundle consists of 1 to 10 single-walled carbon nanotubes.

3. The high solid content single-walled carbon nanotube aqueous conductive paste composition according to claim 2, characterized in that: The single-walled carbon nanotube has a diameter of 1.3-2.0 nm and an aspect ratio of >1000.

4. The high solid content single-walled carbon nanotube aqueous conductive paste composition according to claim 1, characterized in that: The dispersant is sodium carboxymethyl cellulose with a substitution degree of 0.55 to 1.

05.

5. The high solid content single-walled carbon nanotube aqueous conductive paste composition according to claim 1, characterized in that: The pH regulator is a multifunctional amine auxiliary agent AMP-95.

6. The high solid content single-walled carbon nanotube aqueous conductive paste composition according to claim 1, characterized in that: The comb-like polyamide lithium salt is prepared by the following steps: Methoxy polyether amine and 3,3',4,4'-benzophenone tetracarboxylic dianhydride are stirred and dissolved with N,N-dimethylformamide respectively, 35wt% of methoxy polyether amine solution is added into a reaction kettle, 9.5wt% of 3,3',4,4'-benzophenone tetracarboxylic dianhydride solution is added dropwise into the reaction kettle at 45-50°C and 200-300r / min, lithium carbonate is added after the addition is completed, the reaction is stirred at 70-75°C for 2.5-3h, the reaction is cooled to -10°C, filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a comb-like polyamide lithium salt.

7. The high solid content single-walled carbon nanotube aqueous conductive paste composition according to claim 6, characterized in that: The usage ratio of the methoxy polyetheramine solution, the 3,3',4,4'-benzophenone tetracarboxylic dianhydride solution and lithium carbonate is 20 mL:20 mL:0.1 g.

8. The method for preparing a high solid content single-walled carbon nanotube aqueous conductive paste composition according to claim 1, characterized in that: The steps include: Step 1: Mix the dispersant, dispersing aid and deionized water, perform ultrasonic dispersion for 15 to 20 minutes, and adjust the viscosity of the dispersion to 300 to 1000 cps to obtain a dispersion medium; Step 2: Mix the single-walled carbon nanotube powder and the dispersion medium evenly, transfer them to a mixing and degassing machine, stir and degas at a vacuum degree of -30 to -80 kPa and a stirring speed of 1500 to 2000 r / min, and then transfer them to a three-roll mill for grinding and dispersion 1 to 3 times to obtain a single-walled carbon nanotube pre-dispersion; Step 3: Add the pH regulator and deionized water into the single-walled carbon nanotube pre-dispersion according to the raw material ratio, transfer it to a high-pressure microfluidizer and homogenize and disperse it at a homogenization pressure of 600-1000 bar to obtain a high-solid single-walled carbon nanotube aqueous conductive slurry formula composition.

9. The method for preparing a high solid content single-walled carbon nanotube aqueous conductive paste composition according to claim 8, characterized in that: The three-roller grinding machine comprises three rollers, namely roller No. 1, roller No. 2 and roller No. 3, the roller diameters are 50 mm to 120 mm, the rollers are made of zirconia ceramics, and the runout accuracy is 1 um.

10. The method for preparing a high solid content single-walled carbon nanotube aqueous conductive paste composition according to claim 8, characterized in that: The specific method of the grinding and dispersing is as follows: Set the gap between roller No. 1 and roller No. 2 to 300um, the gap between roller No. 2 and roller No. 3 to 150um, and grind 1 to 3 times at a speed of 500rpm; set the gap between roller No. 1 and roller No. 2 to 150um, the gap between roller No. 2 and roller No. 3 to 75um, and grind 1 to 3 times at a speed of 500rpm; set the gap between roller No. 1 and roller No. 2 to 50um, the gap between roller No. 2 and roller No. 3 to 25um, and grind 1 to 3 times at a speed of 500rpm; set the gap between roller No. 1 and roller No. 2 to 20um, the gap between roller No. 2 and roller No. 3 to 10um, and grind 1 to 3 times at a speed of 500rpm to complete grinding and dispersion.

Citation Information

Cited By

  • Carbon nanotube slurry and preparation method thereof

    CN121260553A

  • Preparation method of single-walled carbon nanotube slurry, single-walled carbon nanotube slurry and application thereof

    CN121493953A

  • Method for preparing single-walled carbon nanotube paste, single-walled carbon nanotube paste, and use thereof

    CN121493953B

  • High-solid-content single-walled carbon nanotube slurry as well as preparation method and application thereof

    CN121662818A

  • A high-solids-content single-walled carbon nanotube slurry, its preparation method and application

    CN121662818B